SMS GATEWAY BASED ATTENDANCE MANAGEMENT INFORMATION SYSTEM AS STUDENT ATTENDANCE DATA CONTROL MEDIA AT AL QOLAM TANGGAMUS VOCATIONAL SCHOOL - Manurung, Perdi (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2020)
Along with the development of communication technology and information systems, an increasing number of attendance systems and academic information is being made. In the implementation of this application, at the initial stage, the user must register his identity by using an attendance application program that was built with the PHP programming language, then the attendance data is stored in the My SQL database which has been integrated with the SMS Gateway through the SMS sending software. In addition, with SMS Gateway technology, parents will find it easier to obtain attendance information for their children. From the student side, it is hoped that this application will foster a more disciplined attitude in terms of time because this application will indirectly foster a timely mental attitude in students, and it is hoped that this application can fix any deficiencies in the attendance application that has been implemented earlier.